2001
DOI: 10.1161/hy1201.099611
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Arterial Hypertension

Abstract: Increased vascular reactive oxygen species production, especially superoxide anion, contributes significantly in the functional and structural alterations present in hypertension. An enhanced superoxide production causes a diminished NO bioavailability by an oxidative reaction that inactivates NO. Exaggerated superoxide levels and a low NO bioavailability lead to endothelial dysfunction and hypertrophy of vascular cells. It has been shown that the enzyme NAD(P)H oxidase plays a major role as the most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
243
0
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(266 citation statements)
references
References 78 publications
12
243
0
11
Order By: Relevance
“…Persons with hypertension are at an increased risk for stroke, heart disease, kidney failure, and premature mortality. Free radical induced oxidative stress in part contributes to endothelial dysfunction and development of hypertension [169]. Increased ROS generation eliminates NO • by forming ONOO -, thus reducing NO • bioavailability which leads to decreased endothelium-dependent vasodilation resulting in hypertension [170].…”
Section: Hypertension (Ht)mentioning
confidence: 99%
“…Persons with hypertension are at an increased risk for stroke, heart disease, kidney failure, and premature mortality. Free radical induced oxidative stress in part contributes to endothelial dysfunction and development of hypertension [169]. Increased ROS generation eliminates NO • by forming ONOO -, thus reducing NO • bioavailability which leads to decreased endothelium-dependent vasodilation resulting in hypertension [170].…”
Section: Hypertension (Ht)mentioning
confidence: 99%
“…Endothelial cell dysfunction is often associated with hypertension, due to elevated levels of shear stress. Higher levels of shear stress have been shown to damage the endothelium resulting in increased ROS formation, including O 2 ·- (Zalba et al 2001). …”
Section: Hypertensionmentioning
confidence: 99%
“…The reduction in nitric oxide availability is tied to increased O 2 ·-levels, mainly contributed by NADPH oxidase in smooth muscle cells, resulting in NO intereaction with O 2 ·-and the formation of peroxynitrite (ONOO -, (Landmesser et al 2002;Rathaus et al 2002). Loss of the NO-O 2 ·-balance results in cellular damage, contributing to hypertension and the loss of endothelial cell control of vessel dilation (Zalba et al 2001). Angiotensin II also stimulates NADPH oxidase formation of O 2 ·-, resulting in dysfunctional endothelial cells as discussed above (Hanna et al 2002;Landmesser et al 2002;Rocic et al 2003).…”
Section: Hypertensionmentioning
confidence: 99%
“…In hypertensive patients, vascular smooth muscle cells (VSMCs) from resistance arteries have increased ROS generation, and this increase is linked to NADPH oxidase [16]. Evidence has shown that in SHR and SHRSP rats there was an enhanced production of superoxide (·O 2 ˉ) derived from NADPH oxidase, and this was associated with the upregulation of p22 phox mRNA expression in the aorta [14,17]. Furthermore, NOX2 mRNA expression in the aorta was found to be greater in SHR compared to the normotensive WKY rats [18].…”
Section: Introductionmentioning
confidence: 99%